Environmental Settings of Three Recreation Forests and Their Effects on Visitors' Perception - Yahya, Noor Azlin (1999)
The Recreation Forests of Malaysia are mostly frequented by the middle income residents. It was shown that there are numerous visitors to these sites especially during the weekends. The study looks at the effects of recreational settings, which are the natural resources conditions and the crowding conditions on visits' satisfaction. The excessive use was found to have affected the natural resources and the crowding levels were found to be very high. However, the study found that visitors are still highly satisfied with the recreation experience. Visitors' perceptions of the environmental conditions were assessed for three Recreation Forests namely Sungai Chongkak, Lentang and Sungai Tua which are popular among the population of the Klang Valley. Visitors' preferences and awareness were compared to actual conditions of the Recreation Forests. Findings on awareness, shows that visitors are more aware of the plant component resource more than the other parameters. By groups, it was found that age seems to be a factor in perceiving environmental conditions, where the older people tend to be more aware of the situation. Visitors' environmental preferences are more towards general conditions in term of cleanliness from rubbish and the availability of recreation facilities. They are less affected by crowd as indicated by what they consider as "pollutants" of the Recreation Forests. It was found that visitors object more to hearing noise from other visitors than seeing the crowd. On placing importance, measured in terms of money and walking distance, visitors would rather spend more for cleanliness than for solitude. They are willing to pay up to RM 1 for cleanliness, which was encouraging as the mode. However, nothing at all is willing to be spent for solitude. More visitors are willing to walk for cleanliness (500 m) but not at all for solitude conditions. This again emphasised the lack of importance of solitude, or the lack of aversion to crowd by Recreation Forests' visitors. In fact, when asked what is their crowd tolerance limit, most visitors answered "Do not care". Another finding from this study, is that campers which include visitors of challenging activities are quite different in their perceptions and preferences of environmental conditions. The limit of crowd tolerance is less, and this group made up the most willing to pay up to RM10 and walk up to 1 km. In conclusion, it was found that the recreational settings do indicate excessive use of the area. The natural ecology of the areas is significantly affected, and crowding is intense. It was found that, visitors noticed the conditions of crowding more than the natural resources'. Nevertheless, the majority of visitors are still very satisfied of the recreation experience in the Recreation Forests.